A mixed elastohydrodynamic lubrication model based on virtual rough surface for studying the tribological effect of asperities. Issue 2 (12th March 2018) - Zhang, Hui; Dong, Guangneng; Dong, Guozhong
Abstract : Purpose: The main purpose of this paper is to present the effort on developing a mixed elastohydrodynamic lubrication (EHL) model to study the tribological effect of asperities on rough surface. Design/methodology/approach: The model, with the use of the average flow Reynolds equation and the K-E elasto-plastic contact model, allows predictions of hydrodynamic pressure and contact pressure on the virtual rough surface, respectively. Then, the substrate elastic deformation is calculated by discrete convolution fast-Fourier transform (DC-FFT) method to modify the film thickness recursively. Afterwards, corresponding ball-on-disk tests are conducted and the validity of the model demonstrated. Moreover, the effects of asperity features, such as roughness, curvature radius and asperity pattern factor, on the tribological properties of EHL, are also discussed though plotting corresponding Stribeck curves and film thickness shapes. Findings: It is demonstrated that the current model predicts very close data compared with corresponding experimental results. And it has the advantage of high accuracy comparing with other typical models. Furthermore, smaller roughness, bigger asperity radius and transverse rough surface pattern are found to have lower friction coefficients in mixed EHL models. Originality/value: This paper contributes toward developing a mixed EHL model to investigate the effect of surface roughness, which may be helpful to better understand partial EHL.